Potassium Content and the Balance Between Potassium and Other Minerals and Crude Protein in Forage Can Have a Big Impact on Dairy Cow Health - Eriksson, Hary (UKnowledge, 2023)
Preliminary studies indicated that the mineral balance in forage may affect dairy cow health. A bigger study covering the four most northern counties in northern Sweden was conducted. The objective of this study was to compare data on harvested forage with farm data on milk yield and animal health.